Studi Pemanfaatan Fasilitas Rantai Dingin di Pelabuhan Perikanan Samudera Bungus, Sumatera Barat - Sitanggang, Earline Margareth Br; Nurhayati, Nurhayati; Ramadan, Fauzan; Lisna, Lisna; Ramdhani, Farhan; Nur, Puti (Torani Journal of Fisheries and Marine Science, 2025)
Cold chain facilities, such as ice factories, Air blast freezer (ABF) and cold storage are important components that support improving and maintaining the quality of caught products at the Bungus Ocean Fisheries Port (PPS). This research was carried out at the Samudera Bungus Fishing Harbor on November 4 – November 22 2024. The research method used in this research was the survey method, by distributing questionnaires to users of cooling facilities at PPS Bungus, the number of respondents used was 30 respondents. The results of the research show that in the cold chain facilities at the Bungus Ocean fishing port, 1 unit of ice factory facility with a capacity of 44 tons/day is in good condition. Then there are 3 units of ABF facilities available, consisting of 2 units with a capacity of 3 tons/24 hours freezing in good condition, 1 unit with a capacity of 3 tons/24 hours in a heavily damaged condition, and finally a cold storage facility of 1 unit with a capacity of 100 tons in good condition. From the results of the analysis that has been carried out, it can be concluded that the level of utilization of cold chain facilities at the Bungus Ocean Fishing Port, namely the ice factory facility is 61.82% in the not optimal category with a satisfaction level of 79% or in the satisfied category, the Air blast freezer (ABF) facility is 18.17% in the not optimal category, and the cold storage facility is 16.35% in the not optimal category.